Conclusions and Discussion - Janine Jongbloed; Mark Levels; Christian Brzinsky-Fay (The Dynamics of Marginalized Youth, 2022)
This conclusion presents some closing thoughts on the concepts covered in the preceding chapters of this book. The book attempts to go beyond existing research on young people who are not in education, employment, or training (NEETs), addressing some of the important limitations that had remained largely unexplored to date. It attempts to tease out the heterogeneity in life-course patterns, individual and institutional correlates, and later consequences of prolonged NEET statuses. In the Netherlands, women were more likely than men to experience Long-term and Late NEET patterns than men. Women with children were not more likely to be Long-term NEET but were more likely to become Late NEET, consistent with the Dutch social norm of making the transition into motherhood at relatively older ages.
Keywords: 330